Effect of exercise intensity on cell-mediated immunity - Suzuki, K.; Hayashida, H. (Sports, 2021)
Moderate-intensity exercise is considered to enhance immune function and to be useful for preventing acute upper respiratory infections and similar conditions. Many people practice low-intensity short-duration exercise with the expectation of a beneficial effect on immunocompetency. However, it is difficult to affirm the existence of definite evidence of such a benefit. In this article, we discuss the effects of low-intensity short-duration exercise on cell-mediated immunity, and contrast them to the effects of high-intensity and long-duration exercise. Whereas high-intensity exercise induces inflammation and reduces cell-mediated immune system function, low-intensity exercise does not appear to have a large effect on either inflammation or cell-mediated immune function. Low-intensity exercises such as walking and yoga, which are helpful to relieve stress, cannot be considered as harmful to the immune system. Although yoga was shown to impose fewer restrictions on breathing and physical strain, the evidence that yoga enhances cell-mediated immunity remains insufficient. Therefore, further studies are needed to examine the exercise mode that may be most effective for improvement of immune functions